Immigration and secular stagnation - Kazuyuki Miyagiwa; Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2019)
We examine the effect of immigration on the host country in the dynamic model that can deal with secular unemployment. Immigration has contrasting effects, depending on the economic state of the host country. If there is unemployment, immigration worsens unemployment and decreases consumption by native residents whereas if full employment prevails, immigration has the effect of boosting consumption while keeping full employment. However, an influx of too many immigrants can turn the host country into stagnation. We also find that immigrants' remittances are harmful to the host country under full employment but beneficial under secular stagnation.
Keywords: F16; F22; F41; 330; Immigration; secular stagnation; unemployment; aggregate demand deficiency; remittances